Pendampingan Pengelolaan Sampah Organik & Anorganik Menjadi Barang Bernilai Ekonomis di PPSD Kedungsantren Campurejo Bojonegoro - Erly Juliyani; Hidayatul Mufidah; Nur Ahid (Jurnal Pengabdian Masyarakat Bestari, 2022)
In this Islamic boarding school, assistance in managing organic and inorganic waste into goods of economic value is carried out to reduce the impact on the environment of the Islamic boarding school. Through the Asset Based Community Development or commonly called ABCD, this waste management assistance is carried out for 1 month, namely strengthening the assets owned. The assets owned are community resources (HR) who are passionate about managing organic and inorganic waste. The methods used are inculturation and 5D (Discovery, Dream, Design, Define, and Destiny). The result of this support is the disposal of waste according to its type. For organic trash into fertilizers and animal feed, as well as for inorganic trash into vases, pencil cases, and makeup.